Genetic Diversity Analysis between Different Varieties of Chickpea (Cicer arietinum L.) Using SSR Markers - Yadav, Summy; Shah, Vaidehi; Mod, Bhavya (International Journal of Applied Sciences and Biotechnology, 2019)
The paper aims at evaluating genetic diversity among genomes of chickpea comprising of 5 different varieties with the help of simple sequence repeats (SSR) molecular markers. Genomic DNA isolated from all varieties was checked with 15 different SSR markers specific for ENDPOINT PCR using PCR based techniques. Amplification bands with different markers enabled identification of the genomic regions responsible for Drought Tolerance in chickpea. All 15 SSR markers chosen gave monomorphic bands. A hierarchical tree was also constructed using UPGMA Dendogram for figuring out the exact genetic distance of cultivars using band amplification data. It depicted GUJ-1 and GUJ-2 are closest of all cultivars. GUJ-5 is at the center having GUJ-3 and UJJAVAL at an almost equal distance but GUJ-5 and GUJ-3 are more related. Physiological data also supported this genetic evidence. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 236-242